Bound-State Solution of s-Wave Klein-Gordon Equation for Woods-Saxon Potential. (12th July 2015) - Olğar, Eser; Mutaf, Haydar
Abstract : The bound-state solution of s-wave Klein-Gordon equation is calculated for Woods-Saxon potential by using the asymptotic iteration method (AIM). The energy eigenvalues and eigenfunctions are obtained for the required condition of bound-state solutions.